2022
DOI: 10.3390/ijms23031049
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen, Flurbiprofen, Etoricoxib or Paracetamol Do Not Influence ACE2 Expression and Activity In Vitro or in Mice and Do Not Exacerbate In-Vitro SARS-CoV-2 Infection

Abstract: SARS-CoV-2 uses the human cell surface protein angiotensin converting enzyme 2 (ACE2) as the receptor by which it gains access into lung and other tissue. Early in the pandemic, there was speculation that a number of commonly used medications—including ibuprofen and other non-steroidal anti-inflammatory drugs (NSAIDs)—have the potential to upregulate ACE2, thereby possibly facilitating viral entry and increasing the severity of COVID-19. We investigated the influence of the NSAIDS with a range of cyclooxygenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…46 Moreover, high concentrations of ibuprofen and flurbiprofen reduced SARS-CoV-2 replication in vitro. 47 Data based on small population cohorts and observational and retrospective studies have consistently shown no association between ongoing NSAID therapy and increased mortality [48][49][50][51] or worsening of clinical outcomes 48,49,[51][52][53] in people with COVID-19 in the general population (ie, inpatient and outpatient population; appendix p 1). Similarly, in people with pre-existing rheumatic disease who were chronically exposed to NSAIDs, the ongoing use of these medicines did not increase the risk of hospitalisation for COVID-19 or COVID-19-related death compared with non-users.…”
Section: Do Nsaids Enhance Susceptibility To Sars-cov-2 Infection?mentioning
confidence: 99%
“…46 Moreover, high concentrations of ibuprofen and flurbiprofen reduced SARS-CoV-2 replication in vitro. 47 Data based on small population cohorts and observational and retrospective studies have consistently shown no association between ongoing NSAID therapy and increased mortality [48][49][50][51] or worsening of clinical outcomes 48,49,[51][52][53] in people with COVID-19 in the general population (ie, inpatient and outpatient population; appendix p 1). Similarly, in people with pre-existing rheumatic disease who were chronically exposed to NSAIDs, the ongoing use of these medicines did not increase the risk of hospitalisation for COVID-19 or COVID-19-related death compared with non-users.…”
Section: Do Nsaids Enhance Susceptibility To Sars-cov-2 Infection?mentioning
confidence: 99%
“…However, this speculation about celecoxib was later contradicted by Terrier et al They reported that only naproxen, among NSAIDS, could inhibit the replication of SARS-CoV-2 by binding to its nucleoprotein and that celecoxib did not possess such properties (Terrier et al 2021 ). Another study by de Burin et al concluded that etoricoxib, a selective COX-2 inhibitor, was capable of reducing the viral load in cells infected with SARS-CoV-2, possibly through downregulation of angiotensin-converting enzyme 2 (ACE2), which is a pivotal receptor for SARS-CoV-2 (de Bruin et al 2022 ), further indicating the effectiveness of COX-2 inhibitors as an adjuvant treatment for COVID-19. Speculation by Khupse et al argues that celecoxib competes with SARS-CoV-2 at binding the host cell's bromodomain proteins (BRD)-2/4 and, thus, abrogates SARS-CoV-2 infection (Khupse and Dixit 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their comprehensive review of immunomodulatory effects of opioids and analgesics, Abdel Shaheed et al report research indicating that some NSAIDs demonstrate in vitro and in vivo anti‐viral activity against SARS‐CoV‐2, focussing particularly on indomethacin. 1 They point out that ibuprofen has not shown such activity, citing the work of Chen et al 2 However, more recent in vitro research in Caco‐2 cells indicates that ibuprofen does indeed suppress SARS‐CoV‐2 viral load, 3 albeit only at higher concentrations than those tested by Chen at al. 2 Flurbiprofen has similar anti‐viral activity at higher concentrations.…”
mentioning
confidence: 99%
“… 2 Flurbiprofen has similar anti‐viral activity at higher concentrations. 3 The emerging evidence base for NSAIDs demonstrating in vitro anti‐SARS‐CoV‐2 activity now includes indomethacin, 1 naproxen, 4 flurbiprofen, 3 and ibuprofen. 3 …”
mentioning
confidence: 99%
See 1 more Smart Citation